Analysis of 18 elements in Alpine goat milk in the first third of lactation - Zvonko Antunović; Željka Klir Šalavardić; Boro Mioč; Josip Novoselec (Mljekarstvo)
The research objective was to examine the influence of the first third of the lactation stage on 18 mineral elements in Alpine goat milk. The research was carried out on 20 goats of the French-Alpine breed, which were on average 5 years old and in the fourth lactation. The goats were monitored on the 30th and the 90th day of lactation. Their milk was analysed for chemical composition by the infrared spectroscopy. By means of inductively coupled plasma (ICP), a total of 18 minerals were analysed (Ca, P, K, Na, K, Mg, Fe, Zn, Cu, Se, Mn, Mo, Co, Cr, Ni, Cd, Pb, As and Hg). The period of milk sampling in the first third of lactation significantly influenced the changes in concentrations of Na, Se, Mo, Cr, Ni and As. Significantly higher concentrations of Na and As were determined in milk sampled on the 90th day, while lower concentrations of Se, Mo, Cr and Ni were determined in milk sampled on the 30th day of the first third of lactation. Analysis of the correlation coefficients between the investigated trace elements and the selected toxic elements in Alpine goat milk showed a significantly positive correlation between Ca:Mg, Ca:P, Ca:Co, Ca:Ni, Ca:Mo; Mg:P, Fe:As, Pb:Cd and P:Ni. In the first third of lactation, Alpine goat milk contained a very low concentration of heavy metals. The described changes indicate that Alpine goat milk is rich in essential elements, while the concentration of toxic elements is very low in the first third of lactation.